Factors affecting sustainable growth for South African high voltage electrical construction companies - Zondi, Simphiwe Travor (My University, 2018)
Keywords: FCM, profit, growth, sustainable, construction, high voltage. The construction industry remains a critical contributor to the South African economy. However, the construction industry performance has been on the decline since 2010. Between 2014 and 2015, revenue declined by 6% while profits declined by 54% for the same period. The 2015 secured order book for the industry also decreased by 4% when compared to the 2014 order book. This decline in performance has put employment in the sector under pressure, as 76,000 jobs were lost between 2014 and 2015. The challenges that have faced the industry in terms of achieving suitable profitable growth within the high voltage segment is investigated in this work. From the Fuzzy Cognitive Mapping (FCM) simulation, it is observed that factors which have a marginal impact on profit and growth are skills development, workload, remuneration, education and experience. The close management of these factors remains critical for achieving sustainable profitable growth in this industry.
MBA
Keywords: Corporations -- Growth. Strategic planning.